A Rare Case of Primary Meningococcal Myopericarditis in a 71-Year-Old Male - Odilia I. Woudstra; Gerard J. J. Boink; Jacobus A. Winkelman; Ron van Stralen (Case Reports in Cardiology)
We describe a case of primary meningococcal C pericarditis with myocardial involvement in a 71-year-old male that is thus far the oldest patient with isolated meningococcal pericardial disease and only the third patient with primary meningococcal myopericarditis described in English literature. Our patient was successfully treated by full sternotomy and surgical drainage combined with intravenous ceftriaxone. Mild symptoms unresponsive to anti-inflammatory treatment and leukocytosis may guide clinicians towards the correct diagnosis. It is important to recognize this cause of pericarditis as the relatively mild clinical presentation may rapidly progress into tamponade and right-sided heart failure.